Immune response to oligopeptide permease A (OppA) protein in pigs naturally and experimentally infected with Haemophilus parasuis. (August 2016) - Macedo, Nubia; Oliveira, Simone; Torremorell, Montserrat; Rovira, Albert
Abstract: Haemophilus parasuis is an important swine pathogen that causes Glasser's disease, characterized by pneumonia, polyserositis and meningitis. Protection against H. parasuis infection is associated with the presence of homologous antibodies in serum. However, a H. parasuis antigen that can elicit a protective immune response against all H. parasuis strains has yet to be found. A novel immunogenic and species-specific H. parasuis protein was identified by screening H. parasuis whole cell proteins using swine convalescent sera. One protein of 52 kDa was clearly immunodominant and conserved among different H. parasuis strains. This protein was further identified as an oligopeptide permease A (OppA). Because OppA elicited a specific antibody response in pigs that recovered from H. parasuis infection, we investigated its potential role in diagnostics and protective immunity. An ELISA test using recombinant OppA (rOppA) as its coating antigen was further developed and tested. H. parasuis specific antibodies to rOppA were detected in serum from convalescent pigs but not in serum from specific pathogen free (SPF) or conventional pigs. Pigs immunized with rOppA protein had robust serological responses. However, the antibodies were not protective against challenge infection. We conclude that OppA is a universal species-specific H. parasuis immunogen, and a good marker for previous systemic infection with H. parasuis . Highlights: Haemophilus parasuis oligopeptide permease A (OppA) was identified by Western blot using swine convalescent sera. Recombinant OppA (rOppA)-based ELISA is useful to track systemic infection against H. parasuis . Immunization with H. parasuis rOppA protein had robust serological responses. Antibodies to rOppA do not protect pigs against H. parasuis challenge.